Pola Pandang Wanita Mandiri Dalam Pembangunan Kota Serba Dimensi Bitung Propinsi Sulawesi Utara - Mangowal, Benny (JBE (Journal of Business and Economics); Volume 9 No.1, 2010 JBE UNKLAB, 2010)
The insight of women is considered unique as it compared to hter other parts physically designed by creator.  This phenomenon of insight for women morely as it referenced to her ways of thinking when it growth, would transformed her intuition to her innovation and creation ability.  In conjunction to the establishment of the city of Bitung, the women’s insight on the other hand, is stated typically significant towards the growing of the city.  In this study, the components of women’s insight, is specified in two parts, the cognitive ability and the motherhood role.  In her cognitive ability the study specified her ability to comprehend, to analize, to synthezise, and to evaluate.  On the other side the study further observe her affective drive as she contributes her lifes to communicate others, as well as towards her drive to grow her phychonotoric ability.  In her motherhood role, the study proves her active role as a mother while she understakes her responsibilities as a public figures, presenter, director, and in her organizationals’ occupation.  Externally she has to own a global concept, social and economics concern, preserve her cultural world, as well as her deal with the growing of teaching and education, religious concern, as well as toward to the maintaining clean city concern of Bitung.  She internally further behaves as a wife of ther husband as she continue to care with her children, maintaining her spendings, and showing her willing to grow her house.  The purposive methods approach used in the study towards the 16% or 75 respondents through interviews and questionnaires, specifies the results of their perceptions that, throughout Bitung there are four county (kecamatan) areas, suchs as North Bitung, Mid Bitung, East Bitung and the South Bitung area.  The study uses average and ranking analytical methods, and foundout that in North Bitung (n=14) they underlines the budger program orderly and the maintenance of their residence with the value 4.357, followed by her role in motherhood and comprehensive factors respectively 4.300.  Respondents from the Mid of Bitung introduce their roles as a mother valued 4.731, and the religious concerns 4.692, and the growing of educational and cultural conservation as 4.462.  East Bitung (n=28) stressed the importance of cleanliness and healthiness, valued 4.500, followed by motherhood 4.462 and concerns to communicate valued 4.429.  South Bitung directs the factors of religious community service 4.429 and the role of motherhood 4.286, and the womens figures in public as 4.143.  As they grouped in their level, Eselon 3 and 4, Eselon 3 (n=33) shows their shares in motherhood valued 4.688, their religious communities concern with 4.536, environmental concern 4.463, and towards their importance to communicate 4.406.  Respondents Eselon 4 (n=42) prioritizes their environments 4.465 followed by their motherly factors 4.209, actuating 3.628 and lobbying factor towards their superiors as 3.558.  In general a women in the city of Bitung, they have to improve themselves so that they would behave independently useful in joining with the developent of the city externally, aside of her intention to maintain her women’s insights internally at her circle as a mother.